Law Enforcement against Cyberbullying Crimes: A Juridical Review of the Protection of the Transgender Community - Amelia Rahma Agustina; Mochamad Mansur (Fakultas Syariah IAIN Langsa, 2026)
Ideally, the law functions as an instrument to protect all citizens from various forms of violence, including violence occurring in digital spaces. In reality, however, cyberbullying targeting transgender communities continues to occur and has not been effectively addressed through law enforcement mechanisms. Although Indonesia has established a legal framework through the Electronic Information and Transactions Law and related regulations, the implementation of these norms still faces significant normative and structural challenges. This study aims to analyze the legal enforcement of cyberbullying cases targeting transgender communities and to identify factors affecting the effectiveness of legal protection for victims. This research employs a library-based qualitative approach using a normative juridical method, incorporating statutory, conceptual, and case approaches. The findings reveal that law enforcement against cyberbullying remains largely formalistic and has not fully prioritized victim protection, particularly for vulnerable groups. Moreover, weaknesses in legal structure and legal culture further hinder effective enforcement. Therefore, strengthening law enforcement through a human rights–based perspective is essential to ensure that the law delivers substantive justice within increasingly complex digital environments.